Effects of Music Training on the Auditory Working Memory of Chinese-Speaking School-Aged Children: A Longitudinal Intervention Study - Nie, Peixin; Wang, Cuicui; Rong, Guang; Du, Bin; Lu, Jing; Li, Shuting; Putkinen, Vesa; Tao, Sha; Tervaniemi, Mari (Frontiers in Psychology, 2022)
Music expertise is known to be beneficial for cognitive functions and development. In this study, we conducted a one-year music training on school children (n=123, 7–11 years of age before training) in China. Children were assigned to music or second-language after-class training groups. A passive control group was included. Our aim was to investigate whether music training could facilitate working memory (WM) development, compared with second-language training and no training. Before and after the training, auditory WM was measured via digit span (DS) task, together with the vocabulary and block tests of WISC-IV. The results indicated that the performance of the three training/non-training groups did not differ significantly in DS forward scores. Yet, in the DS backward score, results revealed superior development in the music group compared to the other groups. We conclude that music training may benefit the central executive system of WM, as reflected by the DS backward task.